The “polyploid effect” in the breeding of aromatic and medicinal species - Iannicelli, Jesica; Guariniello, Julian; Tossi, Vanesa Eleonora; Regalado, Jose Javier; Di Ciaccio, Lucia Soledad; van Baren, Catalina María; Pitta Alvarez, Sandra; Escandon, Alejandro Salvio (Elsevier, 2020)
The secondary metabolism of plants delivers a wide range of chemical structures with application for a vast array of activities, thus offering opportunities for social and economic development. Polyploidy is the possession of three or more complete sets of chromosomes. The duplication of the genome, and its possible adaptive advantages, has been an important factor in the speciation and evolution of eukaryotes. The generation of synthetic polyploids as a plant breeding strategy has enabled the development of new and improved cultivars. The aim of this paper is to examine the state-of-the-art concerning the application of polyploidization techniques as a breeding tool and its effects on the phenotypical, biochemical and genetic characteristics in some medicinal aromatic plant (MAP) species to explore our current knowledge of the possible mechanisms involved. Over the last years, new studies have demonstrated that autopolyploidization can remodel the transcriptome and the metabolome generating genomic stress. Consequently, polyploidism can also result in a wide spectrum of modifications, both molecular and physiological, with non-linear results and consequences that also depend on the experimental conditions. Likewise, concepts such as genomic shock and genome fluidity are also involved in this phenomenon, which further increase the complexity of the process.